1997
DOI: 10.1177/01454455970214001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Directed Behavioral Family Intervention for Parents of Oppositional Children in Rural and Remote Areas

Abstract: Twenty-four parents of oppositional preschoolers were randomly assigned to either a self-directed behavioral family intervention condition (SD) or to a waitlist control group (WL). The self-directed parent training program, based on self-regulation principles, consisted of a written information package and weekly telephone consultations for 10 weeks. At posttest, in comparison to the WL group, children in the SD group had lower levels of behavior problems on parent report measures of child behavior. At posttre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
135
2
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(153 citation statements)
references
References 29 publications
13
135
2
3
Order By: Relevance
“…The results of this study are consistent with Connell et al (1997) who demonstrated that selfdirected Triple P with minimal therapist contact was useful in reducing disruptive and oppositional behaviour in young children. The variance of the effects for the standard condition in this study is likely to be the result of a lack of statistical power and this certainly warrants a larger scale evaluation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study are consistent with Connell et al (1997) who demonstrated that selfdirected Triple P with minimal therapist contact was useful in reducing disruptive and oppositional behaviour in young children. The variance of the effects for the standard condition in this study is likely to be the result of a lack of statistical power and this certainly warrants a larger scale evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…They also provide a way for parents to obtain information and avoid the social stigma of being seen as an inadequate parent (Smith, Vartanian, DeFrates Densch et al, 2003). Several randomised controlled trials have investigated the efficacy of self-directed parenting interventions in improving both child functioning and parenting practices (Connell, Sanders & Markie-Dadds, 1997;Markie-Dadds & Sanders, 2006;Sanders, Markie Dadds, Tully & Bor, 2000;Webster-Stratton, Kolpacoff & Hollinsworth, 1988). The results suggest a tiered intervention effect with self-directed interventions being significantly more effective than no intervention, but less effective than therapist led interventions in reducing problem behaviour in children and improving parenting practices, making them an ideal early intervention for parents experiencing sub-clinical problems with child behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has provided some support for the efficacy of self-directed BFI in impacting on children's behaviour, as well as parental discipline (for review see Elgar & McGrath, 2003). There is also limited evidence to suggest that BFIs can have a broader impact on parental personal and marital adjustment (e.g., Connell, Sanders, & Markie-Dadds, 1997;Sanders et al, 2000). This study has provided evidence for the effectiveness of BFI implemented in a regular service delivery context.…”
Section: Discussionmentioning
confidence: 76%
“…Not only have child conduct problems been shown to reduce significantly with BFI, but there is increasing evidence of positive collateral effects in other areas of family functioning as well, including reduced marital conflict over parenting (Dadds, Schwartz, & Sanders, 1987), parental distress such as depression and stress (Connell, Sanders, & Markie-Dadds, 1997;Sanders & McFarland, in press), parental anger and hostility (Sanders & Gravestock, 2000), and increased parental sense of competence (Connell et al, 1997). Many of the main findings of parent training studies have been replicated across many different investigators.…”
Section: The Strengths and Limitations Of Parenting Interventionmentioning
confidence: 99%